(untitled) (Biological Sciences - PJSIR, 2008)
The investigations of the silkworm (Anaphe infracta) larvae on dry weight basis showed that total ash, crude fat and fibre values were low while crude protein and carbohydrate values were high. Fe, Zn, Mg and P were high while Na, Cu, Ni, K, Ca, Mn, Co, Cr were low. The lowest gelation concentration varied between 6.0 in 1.0% Na2SO3 and 14.0 in 20.0% NaCl, NaNO3 and Na2CO3 with low CV%. All the water absorption capacity values were generally high, the highest being in NaNO3. The oil emulsion capacities were generally low whereas the oil emulsion stability was good in all the salts. The isoelectric point under pH solubility depended on the type of salt solution under consideration. These results make A. infracta larvae useful in some food formulations.